2017
DOI: 10.1177/0146167217733069
|View full text |Cite
|
Sign up to set email alerts
|

Friends With Performance Benefits: A Meta-Analysis on the Relationship Between Friendship and Group Performance

Abstract: The current article examines if, and under which conditions, there exists a positive relationship between working with friends and group performance. To do so, using data from 1,016 groups obtained from 26 studies, we meta-analyzed comparisons of the performance of friendship groups versus acquaintance groups. Results show that friendship has a significant positive effect on group task performance (Cohen's d = 0.31). Furthermore, this relationship was moderated by group size (i.e., the positive effect of frien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 113 publications
2
18
0
Order By: Relevance
“…We found that, on average, groups performed better in the problem-solving task than the individual members did alone (see Wittenbaum et al, 2004). Our results confirmed previous findings by showing that both individual performance (e.g., Devine & Philips, 2001) and interpersonal attraction (e.g., Beal et al, 2003;Castaño et al, 2013;Chung et al, 2017) predicted group performance. Furthermore, whereas individual performance was associated only with communication, interpersonal attraction was significantly related to communication, cooperation, and conflict (and marginally significantly related to coordination).…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…We found that, on average, groups performed better in the problem-solving task than the individual members did alone (see Wittenbaum et al, 2004). Our results confirmed previous findings by showing that both individual performance (e.g., Devine & Philips, 2001) and interpersonal attraction (e.g., Beal et al, 2003;Castaño et al, 2013;Chung et al, 2017) predicted group performance. Furthermore, whereas individual performance was associated only with communication, interpersonal attraction was significantly related to communication, cooperation, and conflict (and marginally significantly related to coordination).…”
Section: Discussionsupporting
confidence: 89%
“…We conducted the present study to investigate whether and how group performance could be predicted by individual performance and interpersonal attraction, and whether and how directly observed interpersonal behaviors mediate the relations between these variables on the theoretical basis of the input-process-output model. Our study extends previous research because we went beyond examining the relations between the relevant variables in isolation (e.g., Chung et al, 2017;Casey-Campbell & Martens, 2009;LePine & van Dyne, 2001;DeDreu & Weingart, 2003;Hackmann, 2002;Kozlowski & Bell, 2003). Rather, we considered all of the theoretically important variables in one study.…”
Section: The Present Researchmentioning
confidence: 73%
See 3 more Smart Citations